2012
DOI: 10.1111/j.1462-5822.2012.01798.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecotin‐like serine peptidase inhibitor ISP1 ofLeishmania majorplays a role in flagellar pocket dynamics and promastigote differentiation

Abstract: Leishmania ISPs are ecotin-like natural peptide inhibitors of trypsin-family serine peptidases, enzymes that are absent from the Leishmania genome. This led to the proposal that ISPs inhibit host serine peptidases and we have recently shown that ISP2 inhibits neutrophil elastase, thereby enhancing parasite survival in murine macrophages. In this study we show that ISP1 has less serine peptidase inhibitory activity than ISP2, and in promastigotes both are generally located in the cytosol and along the flagellum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…The morphology of the parasites was determined according to previously published methods [3235] (detail in Additional file 1). …”
Section: Methodsmentioning
confidence: 99%
“…The morphology of the parasites was determined according to previously published methods [3235] (detail in Additional file 1). …”
Section: Methodsmentioning
confidence: 99%
“…The ISPs have inhibitory effects against vertebrate macrophage serine proteases, such as neutrophil elastase and one of them (ISP2, [GeneDB: LmjF.15.0510]) has been shown to enhance parasite survival in murine macrophages [49]. The ISPs also inhibit trypsin-like activity of sand fly midguts in-vitro [50]. The possibility of ISPs having an effect on insect midgut proteases in-viv o is currently under investigation in our laboratory.…”
Section: Reviewmentioning
confidence: 99%
“…2 C ). In addition, infection with a cell line that overexpressed ISP2, WT ( pXG-ISP2 ) (28), demonstrated that an excess of ISP2 delayed MPO-specific bioluminescence, which increased only from 4 wk compared with 2 wk during WT and Δ isp2/3 infection (Supplemental Fig. 2 D ).…”
Section: Resultsmentioning
confidence: 99%
“…1 A ). Cell lines that overexpressed ISP2 [WT ( pXG-ISP2 )] were generated via the introduction of an episomal copy of ISP2 into L. major WT (28). Metacyclic promastigotes were isolated from a stationary phase culture by agglutination of other promastigote forms with peanut lectin, as previously described (31).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation